Environmental determinants of human milk composition in relation to health outcomes. (1st February 2022) - Gridneva, Zoya; George, Alexandra D.; Suwaydi, Majed A.; Sindi, Azhar S.; Jie, Ma; Stinson, Lisa F.; Geddes, Donna T.
Abstract: Humans are exposed to environmental factors at every stage of life including infancy. The aim of this mini‐review was to present a narrative of environmental factors influencing human milk composition. Current literature shows lactation is a dynamic process and is responsive to multiple environmental challenges including geographical location, lifestyle, persistent pollutants and maternal factors (ethnicity, diet, stress, allergy and adiposity) that may influence human milk composition in a synergistic manner and should be considered in order to improve infant and maternal outcomes on a populations scale. Further interventional studies on larger international cohorts are needed to elucidate these complex relationships. Lactating women should aim for a healthy lifestyle and maintain a healthy body composition prior to and throughout the reproductive period, including during lactation.